Association between human leukocyte antigen class II alleles and human papillomavirus-mediated cervical cancer in Indian women - Kohaar, Indu; Hussain, Showket; Thakur, Nisha; Tiwari, Pratibha; Nasare, Vilas; Batra, Swaraj; Singh, Veena; Bhambani, Suresh; Das, Bhudev C.; Sarkar, Debi P.; Bharadwaj, Mausumi (Human immunology, 2009)
We investigated the association of human leukocyte antigen (HLA) II (DRB1 and DQB1) alleles with susceptibility to human papillomavirus (HPV)-associated cervical precancer and cancer cases in a hospital-based case–control study in a northern Indian population. A total of 202 subjects, including 100 patients comprising 31 cervical precancer (cervical intraepithelial neoplasia [CIN] 2/3) and 69 invasive cervical cancer cases, and 102 healthy controls participated in the study. Both patients and controls were screened for HPV infection using a polymerase chain reaction (PCR-based approach. Low-resolution PCR–sequence specific priming (PCR-SSP) was used to genotype HLA II (DRB1 and DQB1). Our results demonstrate that the DRB1*15 allele/DRB1*15-DQB1*06 haplotype may have a predisposition for HPV infection ( p c < 0.05) or cervical cancer/precancer ( p c < 0.05) development, whereas the DRB1*04 allele/DRB1*04-DQB1*03 haplotype might exhibit susceptibility to cervical precancerous lesions ( p c < 0.05). The DRB1*13 allele/DRB1*13-DQB1*06 haplotype was strongly protective against risk to HPV infection ( p c < 0.002) as well as cervical cancer ( p c 0.01). Therefore, we have demonstrated that HLA DR-DQ polymorphisms are involved in genetic susceptibility to cervical cancer or HPV infection in a northern Indian population.